PROSEDUR DAFTAR ULANG IZIN GANGGUAN UNTUK INDEKS GANGGUAN 1 DAN 2 - , HERLAMBANG FADLAN, Dr. Harry Supriyono, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The opening of fourth paragraph of the Constitution of Republic of Indonesia of 1945 mandates the government to strive for peopleâs welfare. Therefore, government is demanded to actively involve in every community life. The most obvious interference of government is giving license. License is made unilaterally by government to direct and control peopleâs activity. Greater authority is given to the government, especially local district/city since the Issuance of Law No. 32 Year 2004 about Regional Government which is stated that the obligatory functions and affairs of choice. Both of these matters are concrete form of government intervention that can be transformed into license. One was the Office of Licensing Service of Sleman District which became a supporting element in Sleman regency administration in implementing the regional administration in the field of licensing services. Field Work Practicum activities which had been implemented for 2 months were able to provide knowledge and experience which were precious. The theory of knowledge during the lecturing can be applied effectively so students will be able to be critical and give a solution when they face the real work world. Field Work Practicum Accountability in the Office of Licensing Service of Sleman Regency named in the form of reflection on the Procedure of Re- Register Hinder Ordonantie for Disorders Index 1 and 2. All matters relating to the background, the subject, the object, the maintenance requirements, the maintenance of procedures up to publishing, and the finance charges related to that reflections became a full authority over the completeness of the Hinder Ordonantie which is undertaken by the Office of Licensing Service of Sleman Regency since 2012.